A comparative study to test the effectiveness of triclosan coated polyglactin 910 in reduction of surgical site infection in clean wounds - Mody, Pratham; Ali, Iqbal; Shetty, Varun; Jadhav, Digvijay; Manerikar, Kshitij; Dikshit, Vashisht (International Surgery Journal, 2019)
Background: Surgical site infection (SSI) has been pointed out as the 2nd most common nosocomial infection. Since suture materials have been proven to be a contributor to SSI, they have been the focus of research and development centered on making them less conducive to bacterial overgrowth. The Triclosan coated suture slowly releases Triclosan, which is an antibacterial agent that inhibits bacterial colonization of the suture and wound site and thus, promises prevention of surgical site infection. Methods: Total of 100 patients undergoing excision of uninfected subcutaneous benign lumps and cutaneous swellings were randomized in two groups: group A in which triclosan coated polyglactin 910 suture was used for wound closure (50 patients) and Group B in whom conventional uncoated Polyglactin 910 suture was used for wound closure (50 patients). Results: In this study, maximum number of patients was in the age group of 46-60 years. Mean age of subjects in triclosan- coated suture group was 45.03 years while it was 47.32 in conventional uncoated suture group. Among 100 subjects in triclosan- coated suture group, 26 (52%) were males and 24 (48%) were females. In comparison to it, male and female subjects in conventional uncoated suture group were 25 (50%) each. Among 50 subjects in triclosan- coated suture group, only 2 (4.0%) had surgical site infection while in conventional uncoated suture group, 8 (16.0%) had surgical site infection. Incidence of surgical site infection with use of triclosan- coated suture was significantly lower compared to conventional uncoated suture group. (p 0.04). Conclusions: Triclosan coated suture surely, helps in preventing surgical site infection which, not only increases the morbidity of the patient but also has long-term implications.